Perfect Capture: Three Takes on Replay, Machinima and the History of Virtual Worlds - Lowood, Henry (Journal of Visual Culture, 2011)
The interactive, immersive and performative aspects of digital games and virtual worlds take the challenges faced by media archivists, curators and historians beyond software preservation to problems that demand new documentation and preservation strategies. The social and performative aspects of online worlds are forcing repositories to develop new strategies for preservation. Of the utmost importance is to preserve and archive practices and performances and not only the software that made these practices and performances possible. The author also argues that the three primary methods for making machinima during its brief history — demo, screen capture, and asset composition — can be matched to three ways for documenting the history of virtual worlds (replay, POV recording, and asset extraction), concluding that machinima provides compelling evidence for the ability of players to turn digital games into their own creative medium.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDcwNDEyOTEwMzkxNTc4